Pengaruh Kepemimpinan dan Komunikasi terhadap Kinerja Karyawan di PT. KLK Dumai - Taufik, Muhammad Irham; Hatta, A Feriansyah; Wendra, Danu (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Effective leadership and communication play an important role in creating a productive and harmonious work environment. This study aims to analyse the influence of effective leadership and communication on employee performance at PT KLK Dumai. Using a quantitative approach, this study involved 30 employees from various sectors to evaluate the relationship between the influence of leadership and communication on employee performance. The result of the coefficient of determination is that the leadership and communication variables are able to explain 49.2% of the model, while the remaining 51.8% is influenced by other models. While the results of the anova output show that the F significance is 0.001, which is <0.0001499 alpha, so it can be concluded that there is a significant influence between the variables X1, X2 with y. Therefore the results showed that leadership and communication have a significant effect on employee performance. Therefore, the results showed that leadership and communication that is open, clear, and reciprocal have a positive correlation with employee performance at PT KLK Dumai.